Stable Micro-Nano Bubble Generation by Low-Power Laser Excitation in a Biocompatible Medium for Drug Delivery - Bunyatova, Ulviya; Doğan, Mustafa; Ferhanoğlu, Onur; Tekin, Engincan; Kilinc, Muhammed (Optica Publishing Group, 2025)
This study demonstrates ultra-stable nano-micro bubbles formed around functionalized silver nanoparticles in a biocompatible medium using low-power laser excitation, achieving over seven-day stability for precise, targeted anti-cancer drug delivery, minimizing side effects.